Age-related hypogonadism and cardiovascular disease risk - N. B. Lebedeva; V. V. Gofman (Фундаментальная и клиническая медицина)
Aim. To study the relationship between age-related androgen deficiency and the level of cardiovascular risk in healthy middle-aged men.Materials and Methods. We enrolled 200 men of 44-55 (median 48.44, interquartile range 45.02- 52.50) years who underwent a routine medical examination, having additionally measured age-related androgen deficiency.Results. A decrease in total testosterone of < 12.1 nmol/L indicative of age-related hypogonadism was detected in 98 (49.0%) men. In 42 (42.8%) men, a decrease in total testosterone was accompanied by loss of libido and erectile dysfunction. Relatively high prevalence of lipid metabolism disorders and subclinical atherosclerosis was diagnosed in men without established cardiovascular disease. Analysis according to the SCORE scale showed a predominance of patients with moderately increased risk, with only a small number of high-risk patients. Notably, all high-risk cases were identified in the age-related hypogonadism group. The distribution of cardiovascular risk score significantly differed in groups with and without age-related androgen deficiency.Conclusion. We demonstrate a relatively high prevalence of age-related testosterone deficiency, which is also associated with increased cardiovascular risk, among healthy middle-aged men.